Impact of a submerged stream groyne on morphology and sedimentology on a tidal inlet, Harle (Southern North Sea, Germany) - Geßner, Anna-Lena; Wollschläger, Jochen; Giebel, Helge-A.; Badewien, Thomas H. (Frontiers in Earth Science, 2024)
Coastal erosion and the need for flood protection present globally significant challenges. To address these challenges, hard coastal protection structures, such as groynes, are employed worldwide to safeguard coastal areas and regulate currents. However, their specific effects on current dynamics and sediment properties, particularly within tidal inlets, remain inadequately investigated, especially in regions like the North Sea characterized by prevalent tidal currents. This study aims to address the knowledge gap by examining the long-term impacts of coastal protection measures on sedimentology, with a focus on the environment of a tidal inlet. The Southern North Sea coast is subject to mesotidal conditions. It presents a mixed-energy coast with an erosive eastward littoral drift, providing an ideal setting for this investigation. On the island of Wangerooge, a prominent groyne extends into the Harle inlet, significantly restricting the exchange area between the North Sea and the Wadden Sea. Consequently, the changes in flow dynamics and sediment transport resulting from the construction significantly affect sediment distribution and morphology within the inlet. Sedimentological analysis was employed to characterize surface sediment properties and statistical analysis identified seven distinct facies associated with three realms, which were shaped by the tidal currents affected by the groyne to a distinct pattern. Additionally, the integration of multibeam data from existing literature facilitated the creation of a comprehensive facies map. These findings suggest alterations in the morphology of the inlet. By comparing the results with an unaffected inlet, the Otzumer Balje, this study provides valuable insights into the complex interplay between coastal protection infrastructure and coastal sedimentology within a high-dynamic tidal inlet system.